Faktor yang Berhubungan dengan Perilaku Kebersihan Diri Saat Menstruasi pada Remaja Putri di SMP Negeri 9 Kota Kupang - Kristina Ermelinda Tanda; Afrona E. L. Takaeb; Petrus Romeo (Yayasan Literasi Sains Indonesia, 2024)
Personal hygiene during menstruation plays an important role in determining a person's health status related to reproductive health. During menstruation, the blood vessels in the uterus become infected very easily because germs enter more easily, resulting in infection which can then cause various disorders or diseases that attack the reproductive organs. This study aims to determine the factors related to personal hygiene behavior during menstruation in adolescent girls at SMP Negeri 9 Kupang City. This type of research is observational analytic with a cross sectional design. The total sample in this study consisted of 75 young women who were selected using proportional stratified random sampling technique with a significance level of α=0.05. Each variable in this study was tested using the chi-square test to determine the relationship between the dependent variable (personal hygiene behavior during menstruation) and the independent variables (knowledge, attitudes, peer support, parental support, teacher support and availability of facilities). The results of this study show that factors related to personal hygiene behavior during menstruation among young women at SMP Negeri 9 Kupang City include attitude (P-value = 0.003), peer support (P-value = 0.001), teacher support (P-value = 0.027), and availability of facilities (P-value = 0.052). Meanwhile, the variable that has no relationship with personal hygiene behavior during menstruation among young women at SMP Negeri 9 Kupang City is knowledge (P-value = 0.367) and parental support (P -value = 0.162). It can be concluded that young women tend to have poor personal hygiene behavior during menstruation.